2013
DOI: 10.1299/jfst.8.247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flow Characteristics of Turbulent Plane Jets Based on Velocity and Scalar Fields Using DNS

Abstract: Turbulent plane jets are prototypical free shear flows on which fundamental research can expand the overall understanding of turbulent flows. In this study, flow characteristics of the turbulent plane jets are studied by means of direct numerical simulation (DNS) based on the finite difference method. The effects of the initial conditions at the jet exit (i.e. Reynolds number and velocity profile) on the spatial development of velocity and scalar fields are mainly investigated. Meanwhile the instantaneous cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Wu et al. (2013) tested top-hat and parabolic profiles of the mean inflow velocity in DNS of a spatially evolving planar jet, and found that the evolution of velocity statistics is different for these profiles. The turbulent intensity defined as at the nozzle exit was also different among experiments and simulations.…”
Section: Direct Numerical Simulation Of a Temporally Evolving Turbulent Planar Jetmentioning
confidence: 99%
“…Wu et al. (2013) tested top-hat and parabolic profiles of the mean inflow velocity in DNS of a spatially evolving planar jet, and found that the evolution of velocity statistics is different for these profiles. The turbulent intensity defined as at the nozzle exit was also different among experiments and simulations.…”
Section: Direct Numerical Simulation Of a Temporally Evolving Turbulent Planar Jetmentioning
confidence: 99%
“…Uniform grids are set in the streamwise and spanwise direction. Non-uniform grids are set in the lateral direction, where the finer grids are set near the jet center, and the change of grid scale follows a hyperbolic tangent function, as used in our previous study (Wu et al, 2013).…”
Section: Governing Equations and Numerical Proceduresmentioning
confidence: 99%
“…In our previous publication (Wu et al, 2013), the Reynolds number dependency was proved important in the evolution of the plane jet. By the analysis of the mean and turbulent data of streamwise velocity and scalar, it is discovered that a large Reynolds number at the jet exit will assist the achievement of self-similarity and the development of turbulence.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sandberg et al [29] computed two-dimensional compressible pipe flow into a co-flow with direct numerical simulation and demonstrated self-preserving behavior of turbulence statistics at nozzle exit. Wu et al [23] analyzed the flow parameters of plane jet based on velocity and scalar fields with direct numerical simulation. Sabra Habli et al [33] showed the effect of the co-flow velocity ratio on two-dimensional turbulent plane jet in co-flow environment using RANS simulation.…”
Section: Introductionmentioning
confidence: 99%